2006
DOI: 10.1099/jmm.0.46219-0
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial pulmonary inflammation due to Microbacterium sp. after heart transplantation

Abstract: A coryneform bacterium was isolated from the bronchoalveolar aspirate of a patient with interstitial pulmonary inflammation. Commercial systems identified the isolate as Corynebacterium sp. or Aureobacterium sp./Corynebacterium aquaticum, but 16S rRNA gene analysis unequivocally attributed it to the genus Microbacterium. This represents the first documented case of Microbacterium pulmonary infection. Case reportA 44-year-old man underwent heart transplantation on 8 August 2000 as a consequence of ischaemic car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
(20 reference statements)
0
15
0
Order By: Relevance
“…Despite this large number of species, only in the mid1990s was the presence of microbacteria in human clinical specimens recognized (7,8,11). Since then, only eight other reports on microbacteria have appeared in the relevant clinical microbiology literature (1,2,9,(12)(13)(14)(15)(16). The aim of the present study was to reveal the distribution of individual Microbacterium species in human clinical specimens by applying phenotypic and molecular genetic methods.…”
mentioning
confidence: 99%
“…Despite this large number of species, only in the mid1990s was the presence of microbacteria in human clinical specimens recognized (7,8,11). Since then, only eight other reports on microbacteria have appeared in the relevant clinical microbiology literature (1,2,9,(12)(13)(14)(15)(16). The aim of the present study was to reveal the distribution of individual Microbacterium species in human clinical specimens by applying phenotypic and molecular genetic methods.…”
mentioning
confidence: 99%
“…In the present case, the commonly used API Coryne system was inconclusive and identification was confirmed by molecular methods (16S rRNA gene sequencing). Limitations of the API Coryne system in the identification of L. aquatica and related species have been reported previously (Winn et al, 2006;Lau et al, 2002;Saweljew et al, 1996;Giammanco et al, 2006). Another study including 178 clinical isolates of Gram-positive rods revealed that 25 % of the strains required additional tests for their identification and 9 % were incorrectly classified (Almuzara et al, 2006).…”
Section: Discussionmentioning
confidence: 81%
“…In spite of the large number of species, few studies have been published on Microbacterium species in the relevant clinical microbiology literature. Microbacterium species, except for Microbacterium resistens, Microbacterium hominis, Microbacterium paraoxydans, and Microbacterium binotii, were initially defined by strains that originated from the environment, and only a small number of species were found to be the causative agents of infections, not only for sporadic infections, but also for nosocomial outbreaks of bacteremia caused by Microbacterium species (Adderson et al, 2008;Alonso-Echanove et al, 2001;Funke et al, 1998;Giammanco et al, 2006;Hirji et al, 2003). Outbreaks of Microbacterium species among cancer patients have indicated their potential to cause morbidity and mortality in immunocompromised patients, suggesting the potential for nosocomial dissemination (Alonso-Echanove et al, 2001).…”
Section: Introductionmentioning
confidence: 99%